Communication Strategy in Handling Baggage Complaints at Citilink Airline in an Indonesian International Airport - Gallis Nawang Ginusti; Erika Puspita Sari (Jurnal Manajemen Dirgantara, 2024)
Baggage issues are occasionally unavoidable during air travel. Ideally, airlines should handle baggage complaints well. However, various issues can arise during the handling process, as experienced by Lost & Found officers at Citilink Airline, especially at international airports while serving global passengers. The objective of this research is to identify the challenges in handling damaged and lost baggage and to examine the communication strategy employed by the officers in addressing Citilink passenger complaints. This is a descriptive qualitative research study using primary data obtained from observation and interviews conducted at the Lost & Found Office PT Gapura Angkasa at one of Indonesia's major international airports during February-March 2023. The analysis covered data collection, reduction, display, and conclusion drawing. To enhance trustworthiness, triangulations were employed throughout the research process. The research indicates three primary challenges faced by the officers such as difficulties in identifying the locus of the damage to the baggage, language barriers during servicing international passengers from different cultural and language backgrounds, and passenger expressions of displeasure and anger. To address the complaints regarding baggage handling, the officers have introduced a sound handling strategy. They listen carefully, apologise sincerely, remain calm during interactions, defuse passengers' anger and ensure that each complaint is handled objectively, efficiently gather the necessary passenger details for communication and compensation purposes, and resolve baggage issues promptly to avoid passenger inconvenience.